2011
DOI: 10.1002/jmri.22587
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of cardiac output and left ventricular function by noninvasive phase‐contrast and cine MRI: Validation study with invasive pressure‐volume loop analysis in a swine model

Abstract: Purpose: To validate noninvasive cardiac output measurements of phase-contrast magnetic resonance imaging (PC-MRI) and cine MRI using an invasive pressure-volume (PV) loop technique on a swine model. Materials and Methods:We compared three methods for evaluating cardiac function at rest and under pharmaceutical low-dose inotropic infusion conditions: 1) phasecontrast MRI, 2) cine MRI, and 3) PV loop relationship. These measurements were made in 14 domestic pigs under rest conditions. Identical MRI acquisitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…CMR can overcome the limitations of TTE and provides the best non-invasive method for measurements of SV and CO. Previous reports have showed that CMR-derived CO had good accuracy and reproducibility compared with RHC-derived CO [24], [25], [26]. In this study, our findings also showed the reasonable agreement between CMR and RHC, and further corroborated the previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…CMR can overcome the limitations of TTE and provides the best non-invasive method for measurements of SV and CO. Previous reports have showed that CMR-derived CO had good accuracy and reproducibility compared with RHC-derived CO [24], [25], [26]. In this study, our findings also showed the reasonable agreement between CMR and RHC, and further corroborated the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Since PVR is directly related to trans-pulmonary pressure gradient (MPAP–PCWP) and inversely related to CO, the non-invasive PVR can be achieved by non-invasive estimation of (MPAP–PCWP) and CO, respectively. It has been previously demonstrated that TTE estimated MPAP and PCWP reliably, but its ability to calculate CO was not as accurate and reproductive as CMR [25], [26]. In this study, our findings also proved the flaw of 2D-TTE in the measurement of CO. On the contrary, CMR was the best non-invasive modality to measure CO but its ability to determine MPAP/PCWP was limited [13], [32].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Indeed, studies on agreement and correlation between different imaging techniques (e.g. MRI, echocardiography) and volumes measured by PV methods in both small‐ and large‐animal models are inconsistent (Amirhamzeh et al 1996; Feldman et al 2000; Jacoby et al 2006; Nielsen et al 2007; Winter et al 2008; Porterfield et al 2009; Lin et al 2011). It should be noted, however, that 3DE moderately underestimates absolute LV volumes in comparison to MRI (Dorosz et al 2012; Greupner et al 2012), which could partly explain the overestimation by the AS of both EDV and ESV at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“… LV mass: excellent validation against gold-standard in animals and excised human hearts after transplantation (Additional file 1 : Table 3ai.1). LV function/cardiac output: limited validation against invasive conductance catheters [ 8 , 9 ] …”
Section: Ventricular Volumes and Massmentioning
confidence: 99%